'It's not right for boys to play with dolls': young children constructing and policing gender during 'free play' in a South African classroom. Issue 4 (4th July 2018) - Mayeza, Emmanuel
ABSTRACT: This paper focuses on the ways in which five- to seven-year-old primary school children in a Black/African township in South Africa construct and experience 'free play' in the classroom. Findings highlight the gendered manner in which play is constructed and constantly policed by these young children during 'free play'. By foregrounding the young children's gendered constructions and experiences of 'free play', the paper challenges the common sense teacher perceptions and constructions of children's play that suggest children have 'free choice'. The paper reveals that play is far from a 'free' activity as it is heavily constrained by specific contextual gender norms and expectations which limit possibilities by reproducing polarised versions of gender and perpetuate gender inequalities. Implications focus on the ways in which teachers can work with children to challenge the boundaries of gender during 'free play'.